An evaluation of intravenous antibiotic preparation and administration by staff nurses of Kenanga 4C Medical Ward in Sultanah Bahiyah Hospital / Sharifah Farahah Syed Isa, Nor Mushaibah Muhamad Fauzi and Muhammad Zikri Budiman Abdul Halim - Syed Isa, Sharifah Farahah; Muhamad Fauzi, Nor Mushaibah; Abdul Halim, Muhammad Zikri Budiman (2010)
The aim of the present study is to assess the appropriateness of parenteral antibiotics preparation and administration by nursing staff in the medical ward of Sultanah Bahiyah Hospital. Utilizing direct observation as the principal method of study, the present investigation also utilized interview method for triangulation purpose. The study was conducted at Kenanga 4C Medical Ward of Sultanah Bahiyah Hospital, Alor Star for a period of two months. Based on the statistical analysis conducted, the results show that most of the nurses did not adhere to the standard practices in which the overall error rate found was 97.3%. Among the four variables that were observed, infusion rate was found to be the highest in terms of error committed (53.4%) followed by concentration errors (25.5%) and mode of IV administration (11.3%). Meanwhile, diluents compatibility for reconstitution and dilution recorded error rates of 7.8% and 2.0% respectively. As a conclusion, the findings of the study have provided evidence that preparation and administration errors do occur in almost all of the parenteral antibiotics administered to the patients involved in the study. Those errors may affect the drug efficacy and may lead to emergence of microorganism resistant. Furthermore, it will expose patients unnecessarily to adverse drug events. Thus, a guide to preparation and administration of intravenous antibiotics drugs should be made available and be distributed to each ward to reduce such errors.